On naive Bayes in speech recognition - Tóth, László; Kocsor, András; Csirik, János (Zielona Góra: Uniwersytet Zielonogórski)
The currently dominant speech recognition technology, hidden Markov modeling, has long been criticized for its simplistic assumptions about speech, and especially for the naive Bayes combination rule inherent in it. Many sophisticated alternative models have been suggested over the last decade.
Keywords: naive Bayes; segment-based speech recognition; hidden Markov model